Distributed computing: Principles and applications. M. L. Liu : Addison-Wesley, 2004. ISBN 0-201-79644-9 - Tinetti, Fernando Gustavo (2006)
Such as the author states in the first pages, this book is the result of several years of teaching the involved topics at the California Polytechnic State University (Cal Poly), San Luis Obispo, California, U.S.A, to undergraduates. This characteristic can be observed in the organization of the book, in each of the chapters, and in the "hands-on" orientation of each of the presented topics. (Párrafo extraído del texto a modo de resumen)